Sight glass with easy-to-clean function and application thereof

By spraying TiO2/SiO2-doped composite nanomaterial on the glass glass, an easy-to-clean coating is formed, which solves the problem of the glass glass being easily contaminated during long-term use, and achieves higher cleaning and observation reliability.

CN119430677APending Publication Date: 2025-02-14HUANENG POWER INT INC DALIAN POWER PLANT +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411568367.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing glass glasses are easily contaminated by resin fragments and dust during long-term use, resulting in difficulty in observation and failure in identification, affecting the reliability of resin transmission and liquid level height.

Method used

TiO2/SiO2 doped composite nanomaterials are used as nanocoatings and sprayed on the surface of plexiglass or quartz glass to form an easy-to-clean coating, improving anti-dust adsorption and anti-static adsorption capabilities.

Benefits of technology

It realizes easy cleaning and high definition of the glass surface of the view mirror, reduces dust and resin residues, and improves the reliability of resin transmission and liquid level observation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430677A_ABST
    Figure CN119430677A_ABST
Patent Text Reader

Abstract

The invention discloses sight glass with an easy-to-clean function and application of the sight glass, the sight glass with the easy-to-clean function provided by the invention not only can be used for observing the internal resin transmission condition and the liquid level height, but also has the properties of easy cleaning and dust adhesion resistance, the realization of the function is benefited from the functionality of a nano coating, and the service life of the sight glass is prolonged. When water falls on the surface, a thin water film is formed, stains adhered to the surface are uniformly washed away, dispersed water drops are not formed, and the high definition of the surface of the sight glass is kept. In addition, the nano coating on the surface of the sight glass has antistatic adsorption capacity, so that dust is not easy to adhere, and the reliability of resin conveying and liquid level observation is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment, and in particular relates to a mirror glass with an easy-to-clean function and application thereof. Background Art

[0002] Industrial sight glass is a kind of perspective window glass for observing the internal medium. It is widely used in pipelines, valves, cracking furnaces, liquid storage tanks and other pressure vessels and instruments in the petroleum, chemical, pharmaceutical, electric power and other industries. In the condensate polishing system of thermal power plants, high-speed mixed beds, regeneration equipment and resin transmission pipelines are installed with sight glass to observe the transmission of resins, liquid level height, etc. However, cation and anion exchange resins inevitably produce broken resins during long-term operation. After being contaminated, they are very easy to adhere to the inside of the sight glass to produce wall hanging phenomenon, which has a great impact on the resin transmission process and endpoint judgment observation.

[0003] In addition, dust in the air adheres to the outer surface of the mirror glass through electrostatic adsorption. The mirror glass at the lower part can be cleaned with a cleaning cloth, but the mirror glass at the higher part is basically not cleaned. Under long-term action, the dust accumulated on the surface of the mirror glass gradually increases, which makes observation difficult. At present, the technology based on intelligent recognition of resin images uses intelligent monitoring equipment to obtain image data through the mirror glass, so as to achieve precise control of the resin delivery endpoint and delivery amount. However, if problems such as resin hanging on the wall and the mirror glass being blocked by dust occur during the recognition process, the control effect will be affected, and in severe cases, recognition failure may occur. Therefore, under the condition that external conditions (such as the intrinsic characteristics of the resin and dust in the environment) cannot be changed, improving the performance of the mirror glass becomes an effective means to solve the above problems. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide an easy-to-clean sight glass material.

[0007] To solve the above technical problems, the present invention provides the following technical solutions: an easy-to-clean mirror glass material, characterized in that: the easy-to-clean mirror glass material includes a receiver and a nano coating, the receiver is organic glass or quartz glass, and the nano coating is a composite nano material doped with TiO2 / SiO2.

[0008] As a preferred solution of the easy-to-clean mirror glass material of the present invention, the easy-to-clean mirror glass material has anti-dust adhesion performance and anti-static adsorption ability.

[0009] As a preferred solution of the easy-to-clean mirror glass material of the present invention, the light transmittance of the easy-to-clean mirror glass material can reach 94.10%.

[0010] Another object of the present invention is to overcome the shortcomings of the prior art and provide an easy-to-clean sight glass material for use in a condensate polishing system in a thermal power plant, characterized in that the easy-to-clean sight glass material is used in a high-speed mixed bed, regeneration equipment, and resin transmission pipeline to improve the reliability of resin transmission and liquid level height observation.

[0011] As a preferred solution of the application of the present invention, the application temperature of the easy-to-clean sight glass material in the condensate polishing system of a thermal power plant is 35-85°C.

[0012] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing mirror glass with an easy-to-clean function, which is characterized by comprising:

[0013] Clean the sight glass so that there is no oil film on the surface of the sight glass;

[0014] The nano coating is sprayed on the cleaned mirror glass surface to form an easy-to-clean coating.

[0015] As a preferred solution of the preparation method of the present invention, the nano coating is a TiO2 / SiO2 doped composite nano material.

[0016] As a preferred embodiment of the preparation method of the present invention, the sight glass is organic glass or quartz glass.

[0017] Beneficial effects of the present invention:

[0018] The easy-to-clean sight glass provided by the present invention has the properties of easy cleaning and dust resistance in addition to observing the internal resin transmission and liquid level. The realization of its functions is due to the functionality of the nano coating. When water falls on its surface, a thin water film is formed, which evenly washes away the stains stuck on the surface without forming scattered water droplets, so that the surface of the sight glass maintains high clarity. In addition, the nano coating on the surface of the sight glass has anti-static adsorption ability, which makes dust difficult to adhere, improves the reliability of resin transmission and liquid level observation, and has significant advantages over existing sight glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0020] Figure 1 These are photos of the surface of the easy-to-clean quartz glass material prepared in Example 2 of the present invention after talcum powder is adhered to the surface and after being rinsed with water.

[0021] Figure 2 The following are photos of the surface of the easy-to-clean quartz glass material prepared in Example 3 of the present invention after adhesion of the cation and anion exchange mixed resin and after being rinsed with water.

[0022] Figure 3 This is a photograph of the easy-to-clean quartz glass material surface prepared in Example 3 of the present invention after being adhered with a cation exchange mixed resin and then rinsed with water.

[0023] Figure 4 This is a photograph of the surface of the easy-to-clean quartz glass material prepared in Example 3 of the present invention after being adhered with an anion exchange mixed resin and then rinsed with water.

[0024] Figure 5 These are photos of the surface of the easy-to-clean organic glass material prepared in Example 5 of the present invention after talcum powder is adhered to the surface and after being rinsed with water.

[0025] Figure 6 The following are photos of the surface of the easy-to-clean organic glass material prepared in Example 6 of the present invention after adhesion of the cation and anion exchange mixed resin and after being rinsed with water.

[0026] Figure 7 This is a photograph of the easy-to-clean organic glass material prepared in Example 6 of the present invention after the surface is adhered with a cation exchange mixed resin and then rinsed with water.

[0027] Figure 8 This is a photograph of the easy-to-clean organic glass material surface prepared in Example 6 of the present invention after the anion exchange mixed resin is adhered and then rinsed with water.

[0028] Fig. 9 These are photos of the easy-to-clean glass prepared in Example 7 of the present invention and the glass without surface treatment after being adhered with talcum powder.

[0029] Fig.10 These are photos of the easy-to-clean glass prepared in Example 7 of the present invention and the glass without surface treatment after being adhered with talcum powder and then rinsed with water.

[0030] Fig.11 The mass of talc powder on the surface of the easy-to-clean glass prepared in Example 7 of the present invention and the glass without surface treatment. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] Example 1

[0035] This embodiment provides a method for preparing an easy-to-clean quartz glass material, comprising the following steps:

[0036] Use deionized water to clean the quartz glass and dry it in an oven. Use a dropper to drop water on the surface of the quartz glass. If the surface shows a water film and there is no oil film to touch, the surface treatment can be performed. Spray TiO2 / SiO2-doped composite nanomaterials (Fengshi New Energy, Tianjin Fengshi New Energy Technology Co., Ltd., Jingzhong Tianjin Nano Technology Co., Ltd.) on the surface of the quartz glass, and wipe it with a fiber cloth moistened with nano-coatings. Repeat the operation twice and leave it for 24 hours before use.

[0037] Example 2

[0038] This embodiment is to test the dust adhesion performance of the easy-to-clean quartz glass material prepared in Example 1, comprising the following steps:

[0039] (1) Weigh 0.58 g of 800-mesh talc powder and place it on the surface of the untreated quartz glass and the surface of the easy-to-clean quartz glass. The talc powder on the easy-to-clean quartz glass surface is 0.5831 g, and the talc powder on the untreated quartz glass surface is 0.5831 g. Vibrate the talc powder on the quartz glass surface evenly and observe the talc powder left on the quartz glass surface. Figure 1 As shown in (a), the amount of talc powder on the surface of the easy-to-clean quartz glass is less, and the surface of the quartz glass without surface treatment has talc powder accumulation.

[0040] (2) Use 6 mL of deionized water to rinse the untreated quartz glass surface and the easy-to-clean quartz glass surface respectively. Figure 1 As shown in (b), the surface of the untreated quartz glass forms groove-shaped dust after being washed by water (formed by incomplete water washing), and the easy-to-clean quartz glass surface does not have scale-shaped dust (dust absorbs moisture to form particles with strong adhesion, and scale-shaped dust with a hard crystalline shell after drying) and groove-shaped dust.

[0041] Example 3

[0042] This embodiment is to test the resin adhesion performance of the easy-to-clean quartz glass material prepared in Example 1, comprising the following steps:

[0043] (1) Place the cationic resin and the anionic resin in a mortar for grinding, and mix the cationic resin and the anionic resin in a mass ratio of 1:1. Weigh 0.48g of the ground resin and place it on the surface of the untreated quartz glass and the easy-to-clean quartz glass, respectively. The easy-to-clean quartz glass surface contains 0.4845g of the mixed fat, and the untreated quartz glass surface contains 0.4844g of the mixed fat. Vibrate the mixed fat on the quartz glass surface evenly and observe the amount of the mixed fat left on the quartz glass surface. Figure 2 As shown in (a), no fat-mixed residue was observed on the surface of the easy-to-clean quartz glass, while more residue was observed on the surface of the quartz glass without surface treatment.

[0044] (2) Grind the cationic resin and the anionic resin in a mortar and grind them separately, and then mix the cationic resin and the anionic resin in a mass ratio of 1:1. Figure 2 b) Cationic resin ( Figure 3 a) and anionic resin ( Figure 4 a) Place them on the surface of untreated quartz glass and easy-to-clean quartz glass respectively, and use a syringe to completely flush the mixed fat on the surface of the quartz glass. Figure 2 (c) Figure 3 (b) Figure 4 As shown in (b), the surface of the easy-to-clean quartz glass is clean without water droplets hanging on the wall. On the surface of the quartz glass that has not been surface treated, water droplets adhere to the glass surface, forming a wall hanging phenomenon.

[0045] Example 4

[0046] This embodiment provides a method for preparing an easy-to-clean organic glass material, comprising the following steps:

[0047] Use deionized water to clean the plexiglass and dry it in an oven. Use a dropper to drop water on the surface of the plexiglass. If the surface shows a water film and there is no oil film to touch, the surface treatment can be performed. Spray the TiO2 / SiO2-doped composite nanomaterial on the surface of the plexiglass and wipe it with a fiber cloth moistened with nano-coating. Repeat the operation twice and leave it for 24 hours before use.

[0048] Example 5

[0049] This embodiment is to test the dust adhesion performance of the easy-to-clean organic glass material prepared in Example 4, comprising the following steps:

[0050] (1) Weigh 0.58g of 800-mesh talc powder and place it on the untreated plexiglass surface and the easy-to-clean plexiglass surface respectively. The talc powder on the easy-to-clean plexiglass surface is 0.5802g, and the talc powder on the untreated plexiglass surface is 0.5801g. Vibrate the talc powder on the plexiglass surface evenly and observe the talc powder left on the plexiglass surface. Figure 5 As shown in (a), the amount of talcum powder on the surface of the easy-to-clean plexiglass is less, while the surface of the plexiglass without surface treatment has talcum powder accumulation.

[0051] (2) Use deionized water to rinse the untreated plexiglass surface and the easy-to-clean plexiglass surface respectively. Figure 5 As shown in (b), the untreated plexiglass surface forms groove-shaped dust after being washed by water, while the easy-to-clean plexiglass surface does not have scale-shaped dust and groove-shaped dust.

[0052] Example 6

[0053] This embodiment is to test the resin adhesion performance of the easy-to-clean organic glass material prepared in Example 4, comprising the following steps:

[0054] (1) Grind the cationic resin and the anionic resin in a mortar and grind them respectively, and then mix the cationic resin and the anionic resin in a mass ratio of 1:1. Weigh 0.48g of the ground resin and place them on the surface of the untreated organic glass and the surface of the easy-to-clean organic glass respectively, wherein the mixed fat on the surface of the easy-to-clean organic glass is 0.4803g, and the mixed fat on the surface of the untreated organic glass is 0.4802g. Vibrate the mixed fat on the organic glass surface uniformly and observe the mixed fat left on the organic glass surface, such as Figure 6 As shown in (a), no fat-mixed residue was observed on the easy-to-clean plexiglass surface, while more residue was observed on the untreated plexiglass surface.

[0055] (2) Grind the cationic resin and the anionic resin in a mortar and grind them separately, and then mix the cationic resin and the anionic resin in a mass ratio of 1:1. Figure 6b) Cationic resin ( Figure 7 a) and anionic resin ( Figure 8 a) Place them on the untreated glass surface and the easy-to-clean glass surface respectively, and use a syringe to completely flush the mixed fat on the glass surface. Figure 6 (c) Figure 7 (b) Figure 8 As shown in (b), the surface of the easy-to-clean glass is clean without water droplets hanging on the wall. On the surface of the glass that has not been surface treated, water droplets adhere to the glass surface, forming a wall hanging phenomenon.

[0056] Example 7

[0057] This embodiment is to test the acid resistance of the easy-to-clean glass prepared in Example 4, comprising the following steps:

[0058] Place the glass in 1000mL 4wt% hydrochloric acid solution for 24h, then wash with deionized water and dry. Weigh a certain amount of 800-mesh talcum powder and place it on the glass surface. After vibrating evenly, observe the residual amount of talcum powder. Then use deionized water to rinse the glass surface and observe the cleaning condition of talcum powder. Fig. 9 and Fig.10 It can be seen that the easy-to-clean glass still has obvious anti-dust adhesion performance in an acidic environment, and can be easily washed away by water to remove dust and keep it clean.

[0059] To further test the dust resistance of the acid-treated easy-to-clean glass, the mass of talcum powder on its surface was tested and compared with the talcum powder on the surface of unmodified glass to analyze the dust adhesion of the easy-to-clean glass. Compared with the unmodified glass, the dust mass of the easy-to-clean glass was reduced by 65% ​​( Fig.11 ).

[0060] Comparative Example 1

[0061] The difference between this comparative example and Example 1 is that the nano coating is replaced with nano SiO2, and the rest of the operations are the same as those in Example 1, wherein the preparation method of nano SiO2 refers to Lu Z, Xu L, He Y, et al. Thin Solid Films, 2019, 692: 137560.

[0062] Comparative Example 2

[0063] The difference between this comparative example and Example 1 is that the nano coating is replaced by a TiO2 / CNTs-doped composite nano material, and the remaining operations are the same as those in Example 1, wherein the preparation method of the TiO2 / CNTs-doped composite nano material is referred to Wu Y, Zhou Z, Tuo Y, et al. Materials Chemistry and Physics, 2015, 149-150: 522.

[0064] Comparative Example 3

[0065] The difference between this comparative example and Example 1 is that the nano coating is replaced by TA-CNTs / SiO2 doped composite nano material, and the other operations are the same as Example 1, wherein the preparation method of TA-CNTs / SiO2 doped composite nano material refers to Tan Chunyu, Ye Xiangdong, Xi Changqing, et al. TA-CNTs / SiO_2 black transparent super hydrophilic coating suitable for glass curtain wall and its performance [J]. Fine Chemicals, 2023, 40(12): 2622-2629. DOI: 10.13550 / j.jxhg.20230087.

[0066] Example 8

[0067] This embodiment tests the light transmittance of the glass obtained in Example 1 and Comparative Examples 1 to 3. The test results are shown in Table 1.

[0068] Table 1

[0069] Light transmittance Example 1 94.10% Comparative Example 1 88.70% Comparative Example 2 89.10% Comparative Example 3 60.00% Ordinary glass 91.00%

[0070] At present, the self-cleaning technology basically does not consider the transmittance, but only considers its surface properties (super hydrophilic or super hydrophobic) and anti-fouling performance. For example, the use of some colored materials, although it has the performance of easy cleaning, changes the color of the surface of the mirror, blocks the internal medium, makes it impossible to observe the internal medium, and cannot view the internal medium. The TiO2 / SiO2 doped composite nanomaterial used in the present invention increases the SiO2 component to reduce the reflected light and increase the transmitted light of the glass, thereby improving the transmittance and reducing the influence of light spots and false light sources.

[0071] The easy-to-clean sight glass provided by the present invention has the properties of easy cleaning and dust resistance in addition to observing the internal resin transmission and liquid level. The realization of its functions is due to the functionality of the nano coating. When water falls on its surface, a thin water film is formed, which evenly washes away the stains stuck on the surface without forming scattered water droplets, so that the surface of the sight glass maintains high clarity. In addition, the nano coating on the surface of the sight glass has anti-static adsorption ability, which makes dust difficult to adhere, improves the reliability of resin transmission and liquid level observation, and has significant advantages over existing sight glass.

[0072] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. An easy-to-clean mirror glass material, characterized in that: The easy-to-clean mirror glass material comprises a receiver and a nano coating, wherein the receiver is organic glass or quartz glass, and the nano coating is a composite nano material doped with TiO2 / SiO2.

2. The easy-to-clean mirror glass material according to claim 1, characterized in that: The easy-to-clean mirror glass material has dust-resistance adhesion and anti-static adsorption capabilities.

3. The easy-to-clean mirror glass material according to claim 1, characterized in that: The light transmittance of the easy-to-clean mirror glass material can reach 94.10%.

4. Application of an easy-to-clean sight glass material in a condensate polishing system of a thermal power plant, characterized in that: The easy-to-clean sight glass material is applied to a high-speed mixed bed, a regeneration device and a resin transmission pipeline to improve the reliability of observing the transmission of the resin and the liquid level height.

5. The use according to claim 4, characterized in that: The application temperature of the easy-to-clean sight glass material in the condensate polishing system of a thermal power plant is 35-85°C.

6. A method for preparing mirror glass with easy-to-clean function, characterized in that: include, Clean the sight glass so that there is no oil film on the surface of the sight glass; The nano coating is sprayed on the cleaned mirror glass surface to form an easy-to-clean coating.

7. The preparation method according to claim 6, characterized in that: The nano coating is a TiO2 / SiO2 doped composite nano material.

8. The preparation method according to claim 6, characterized in that: The sight glass is organic glass or quartz glass.